2018
DOI: 10.1053/j.gastro.2018.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Based Differences in Incidence of Inflammatory Bowel Diseases—Pooled Analysis of Population-Based Studies From Western Countries

Abstract: In a pooled analysis of population-based studies, we found age at IBD onset to vary with sex. Further studies are needed to investigate mechanisms of sex differences in IBD incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
125
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 211 publications
(144 citation statements)
references
References 89 publications
13
125
2
4
Order By: Relevance
“…In this respect, our results are in agreement with other studies that have demonstrated that the presenting phenotype of childhood‐onset IBD is characterised by extensive anatomic involvement, in comparison with adulthood‐onset IBD . In addition, in agreement with a recent study published by Shah et al, the proportion of male sex was higher in the childhood‐onset cohort . Second, family history of IBD was more frequent in childhood‐onset IBD, suggesting a higher genetic load in this group of patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this respect, our results are in agreement with other studies that have demonstrated that the presenting phenotype of childhood‐onset IBD is characterised by extensive anatomic involvement, in comparison with adulthood‐onset IBD . In addition, in agreement with a recent study published by Shah et al, the proportion of male sex was higher in the childhood‐onset cohort . Second, family history of IBD was more frequent in childhood‐onset IBD, suggesting a higher genetic load in this group of patients.…”
Section: Discussionsupporting
confidence: 93%
“…24 In addition, in agreement with a recent study published by Shah et al, the proportion of male sex was higher in the childhood-onset cohort. 25 Second, family history of IBD was more frequent in childhood-onset IBD, suggesting a higher genetic load in this group of patients. Third, the use of immunomodulators and biologic agentsafter adjusting by relevant variables such as the type of IBD, sex, tobacco use or family history of IBD-was higher among childhoodonset IBD patients.…”
Section: Discussionmentioning
confidence: 83%
“…Women showed higher global prevalence than men accordingly with previous findings concerning incidence . There was, however, heterogeneity across geographic areas.…”
Section: Discussionsupporting
confidence: 76%
“…3,11,[28][29][30] In a pooled analysis of studies in the West, females predominated among CD patients from adolescence to middle-age, while a higher risk of UC was found among males aged 45 years and older. 33 These findings contrast with those from Asia, where male gender was associated with a higher risk of both CD and UC. In mainland China, the risk ratio of CD and UC in males versus females is 1.15:1 and 2.4:1, respectively.…”
Section: Clinical Features Of Ibdmentioning
confidence: 87%
“…In CD, less consistent findings have been reported, with some cohorts suggesting a female predominance in the incidence of CD and others failing to find any gender difference whatsoever . In a pooled analysis of studies in the West, females predominated among CD patients from adolescence to middle‐age, while a higher risk of UC was found among males aged 45 years and older …”
Section: Clinical Features Of Ibdmentioning
confidence: 94%